PENYULUHAN TENTANG PEMANFATAAN PRIMARY CARE DI PUSKESMAS PATUMBAK KABUPATEN DELI SERDANG - Bahtera Bin David Purba; Rusdi Andreas Sembiring; Nerdy Nerdy; Evalina Manurung (INSTITUT KESEHATAN DELI HUSADA, 2021)
According to Permenkes No. 75/2014 on Community Health Centers, article (1) states that a community health center, hereinafter referred to as a Puskesmas, is a health service facility that organizes public health efforts and individual health efforts at the first level, by prioritizing promotive and preventive efforts. The preliminary survey results at level one health facilities show that there are still problems with the use of the p-care information system, its use is not optimal due to several reasons, one of which is the frequent errors in the P-Care application, namely P-Care officers at the Puskesmas often experience problems when going to the P-Care application. perform BPJS patient data entry, causing officers to double-enter BPJS patient data. Based on the foregoing, the authors are interested in conducting PKM which aims to provide counseling on the use of primary care at the Puskesmas Patumbak, Deli Serdang Regency. Puskesmas has a function for community health development, fostering community participation, providing comprehensive health services. The advantage of using p-care services, a more practical patient registration flow, patient data, integrated patient diagnosis process, faster referral process, easier some of the features of the p-care application: Billing Information, Procedures for Registering BPJS Kesehatan Participants Independently or Agencies, Search for Health Facilities Nearby. The importance of providing counseling on the use of primary care at the Puskesmas Patumbak, Deli Serdang regency, in order to improve the quality of service and patient satisfaction with the health workers in the hospital.